Influence of Shape and Piezoelectric-Patch Length on Energy Conversion of Bluff Body-Based Wind Energy Harvester - Changjiang Zhang; Lin Ding; Lin Yang; Zuomei Yang; Zesheng Yang; Li Zhang (Complexity)
The technology of scavenging ambient energy to realize self-powered of wireless sensor has an important value in practice. In order to investigate the effects of piezoelectric-patch length and the shape of front bluff body on energy conversion of the wind energy harvester by flow-induced vibration, the characteristics of a piezoelectric wind energy harvester based on bluff body are experimentally studied in this work. Four different section shapes of the bluff body, including triangular cylinder, trapezoidal cylinder, reverse trapezoidal cylinder, and square cylinder, are tested. The piezoelectric patch is attached on the leeward side of the bluff body. The lengths of piezoelectric patch are considered as 1.0D–1.4D (D is the characteristic length of the bluff body). It is found that the length of the piezoelectric patch and the shape of the front bluff body play a vital role in improving the performance of wind energy harvester. For the reverse trapezoidal cylinder and square cylinder, the back-to-back vortex-induced vibration (VIV) and galloping phenomenon can be observed. In addition, the energy harvesting performance of the reverse trapezoidal cylinder piezoelectric harvester is the best. The maximum average peak voltage of 1.806 V and the output power of P=16.3 μW can be obtained when external resistance and the length of piezoelectric patch are 100 KΩ and 1.1D, respectively.